A 4-Week Multimodal Intervention for Individuals With Chronic Ankle Instability: Examination of Disease-Oriented and Patient-Oriented Outcomes - Powden, Cameron J. (J Athl Train, 2019)
CONTEXT: Individuals with chronic ankle instability (CAI) experience disease- and patient-oriented impairments that contribute to both immediate and long-term health detriments. Investigators have demonstrated the ability of targeted interventions to improve these impairments. However, the combined effects of a multimodal intervention on a multidimensional profile of health have not been evaluated. OBJECTIVE: To examine the effects of a 4-week rehabilitation program on disease- and patient-oriented impairments associated with CAI. DESIGN: Controlled laboratory study. SETTING: Laboratory. PATIENTS OR OTHER PARTICIPANTS: Twenty adults (5 males, 15 females; age = 24.35 ± 6.95 years, height = 169.29 ± 10.10 cm, mass = 70.58 ± 12.90 kg) with self-reported CAI participated. Inclusion criteria were at least 1 previous ankle sprain, at least 2 episodes of “giving way” in the 3 months before the study, and a Cumberland Ankle Instability Tool score ≤24. INTERVENTION(S): Individuals participated in 12 sessions over 4 weeks that consisted of ankle stretching and strengthening, balance training, and joint mobilizations. They also completed home ankle-strengthening and -stretching exercises daily. MAIN OUTCOME MEASURE(S): Dorsiflexion range of motion (weight-bearing–lunge test), isometric ankle strength (inversion, eversion, dorsiflexion, plantar flexion), isometric hip strength (abduction, adduction, flexion, extension), dynamic postural control (Y-Balance test), static postural control (eyes-open and -closed time to boundary in the anterior-posterior and medial-lateral directions), and patient-reported outcomes (Foot and Ankle Ability Measure–Activities of Daily Living and Foot and Ankle Ability Measure–Sport, modified Disablement in the Physically Active scale physical and mental summary components, and Fear-Avoidance Beliefs Questionnaire–Physical Activity and Fear-Avoidance Beliefs Questionnaire–Work) were assessed at 4 times (baseline, preintervention, postintervention, 2-week follow-up). RESULTS: Dorsiflexion range of motion, each direction of the Y-Balance test, 4-way ankle strength, hip-adduction and -extension strength, the Foot and Ankle Ability Measure–Activities of Daily Living score, the modified Disablement in the Physically Active scale–physical summary component score, and the Fear-Avoidance Beliefs Questionnaire–Physical Activity score were improved at postintervention (P < .001; effect-size range = 0.72–1.73) and at the 2-week follow-up (P < .001; effect-size range = 0.73–1.72) compared with preintervention. Hip-flexion strength was improved at postintervention compared with preintervention (P = .03; effect size = 0.61). Hip-abduction strength was improved at the 2-week follow-up compared with preintervention (P = .001; effect size = 0.96). Time to boundary in the anterior-posterior direction was increased at the 2-week follow-up compared with preintervention (P < .04; effect-size range = 0.61–0.78) and postintervention (P < .04) during the eyes-open condition. CONCLUSION: A 4-week rehabilitation program improved a multidimensional profile of health in participants with CAI.